Investigation of magnetic field signals during vortex-induced pressure drops at InSight. (August 2022) - Thorne, Shea N.; Johnson, Catherine L.; Mittelholz, Anna; Langlais, Benoit; Lorenz, Ralph; Murdoch, Naomi; Spiga, Aymeric; Smrekar, Suzanne E.; Banerdt, W. Bruce
Abstract: The NASA InSight lander has recorded many pressure drops attributed to convective vortices during its first full year of data collection. However, although dust-carrying vortices (dust devils) are a common phenomenon on Mars, they have not been observed in InSight images. On Earth, magnetic signals associated with some dust devils have been reported. Data from the InSight Fluxgate Magnetometer (IFG) provide the first opportunity for similar investigations on Mars. Here, we evaluate whether magnetic signals are associated with daytime vortices. We incorporate observations of environmental conditions, measurements of ground tilt from seismic data, and data from the lander's solar panels, and consider the potential for dust-laden vortices to generate observable magnetic field signals. We find that 7.7% of pressure drop events greater than 1 ​Pa show a resolvable magnetic field signal at the time of the pressure drops. The resolvable magnetic signals, typically seen on the horizontal field components, are less than 1 ​nT in amplitude, and have no clear correlation with local time, duration, or pressure drop magnitude. During nine pressure drop events we found smoothly varying magnetic signals of at least 0.3 ​nT on any one component. To investigate the origin of these magnetic signals we evaluated three possible sources: solar array currents (SAC), ground and lander tilt, and triboelectric effects of lofted dust. We find that SAC and tilt could contribute a change in the magnetic field but cannot solely explain the observed signals. The observed changes in field strength could theoretically be produced via triboelectric effects, but only in the case of exceptionally large dust devils that pass close to the lander. The lack of imaged dust devils and the small number of observed magnetic signatures despite numerous measured pressure drops is consistent with at most a small proportion of dust laden convective vortices at InSight and associated predicted triboelectric effects. Highlights: We investigate magnetic field signatures of vortices on Mars with InSight data. 7.7% of 862 pressure drop events >1 ​Pa exhibit magnetic field signals < ∼1 ​nT. Dust-laden convective vortices in close approach could cause magnetic field signals. Most pressure drop events lack magnetic signals, matching dearth of dust devil images.